Rhodnius prolixus smells repellents: Behavioural evidence and test of present and potential compounds inducing repellency in Chagas disease vectors. (October 2015) - Zermoglio, Paula F.; Martin-Herrou, Hadrien; Bignon, Yohan; Lazzari, Claudio R.
Graphical abstract: Highlights: The efficacy and action mechanism of repellents remain unknown for most insects. We tested commercial and novel molecules on Rhodnius prolixus using three bioassays. Repellents repel R. prolixus by themselves, showing that bugs can smell them. The performance of repellents on bugs differs from that on mosquitoes. We present simple bioassays for testing repellents against Chagas disease vectors. Abstract: Insect repellents are known since many decades ago and constitute a major tool for personal protection against the biting of mosquitoes. Despite their wide use, the understanding of why and how repellents repel is relatively recent. In particular, the question about to what extent insects other than mosquitoes are repulsed by repellents remains open. We developed a series of bioassays aimed to test the performance of well established as well as potential repellent molecules on the Chagas disease vector Rhodnius prolixus . Besides testing their ability to prevent biting, we tested the way in which they act, i.e., by obstructing the detection of attractive odours or by themselves. By using three different experimental protocols (host-biting, open-loop orientation to odours and heat-triggered proboscis extension response) we show that DEET repels bugs both in the presence and in the absence of host-associated odours but only at the highest quantities tested. Piperidine was effective with or without a host and icaridine only repelled in the absence of a living host. Three other molecules recently proposed as potential repellents due to their affinity to the Ir40a + receptor (which is also activated by DEET) did not evoke significant repellency. Our work provides novel experimental tools and sheds light on the mechanism behind repellency in haematophagous bugs.